Explicit consent In the context of personal data processing conditions compared to Turkish law and European law - Akcan Babacan, Hatice Nur (Riga Graduate School of Law, 2022)
Technology, which has developed rapidly in the last century and continues to develop at an increasing speed, has spread to all areas of daily life and has become intricate with life routines. Accordingly, the storage and processing of personal data have become inevitable. This inevitability has brought some rules, control mechanisms, and sanctions. Several national and international regulations guarantee the right to protect personal data. This study is a comparative study on personal data protection law and express consent in Turkey and Europe. The study is generally shaped within the framework of General Data Protection Regulation (GDPR) and Kisisel Verilerin Korunmasi Kanunu (KVKK).
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Other law::Comparative law; Research Subject Categories::LAW/JURISPRUDENCE::Other law::European law; Data protection; General Data Protection Regulation; Turkey; the European Union